2020
DOI: 10.1097/md.0000000000019596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statin use on cancer-specific mortality and recurrence

Abstract: This meta-analysis mainly summarized the studies reporting an association between statin use and cancer-specific mortality and recurrence or progression of cancer patients.We systematically searched for studies about the statin used in cancer patients in electronic databases, including PubMed, Web of Science, Cochrane, Clinical Trials, from inception through the November 2019. A total of 60 studies which included 953,177 participants were eligible with 233,322 cancer patients used statin. Our analysis selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 96 publications
0
16
0
3
Order By: Relevance
“…In addition, pre-clinical data have demonstrated that statins reduce prenylation, a required step in localization and activity of RAS proteins. Statins have therefore been explored in various human disease paradigms that involve deregulation of RAS/MAPK and related signaling axes ( Youssef et al., 2002 ; Davies et al., 2016 ; Yang et al., 2020 ). Importantly, we found that, for some RASopathy variants, the efficacy of some drugs including statins correlated with suppression of pathways outside the canonical RAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-clinical data have demonstrated that statins reduce prenylation, a required step in localization and activity of RAS proteins. Statins have therefore been explored in various human disease paradigms that involve deregulation of RAS/MAPK and related signaling axes ( Youssef et al., 2002 ; Davies et al., 2016 ; Yang et al., 2020 ). Importantly, we found that, for some RASopathy variants, the efficacy of some drugs including statins correlated with suppression of pathways outside the canonical RAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-clinical data has demonstrated that statins reduce prenylation, a required step in localization and activity of RAS proteins. Statins have therefore been explored in various human disease paradigms that involve deregulation of RAS/MAPK and related signaling axes (Davies et al, 2016; Yang et al, 2020; Youssef et al, 2002). Importantly, we found that, for some RASopathy variants, the efficacy of some drugs including statins correlated with suppression of pathways outside the canonical RAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD36 inhibition in ovarian cancer cells reduced their in vitro and in vivo invasive capabilities sustained by CAAs (180). Moreover, Masko et al pointed out that the combination of standard treatments with drugs interfering with adipocyte metabolism, like statins, has promising therapeutic relevance in prostate cancer treatment (181,182). The administration of a high fat diet, instead of a normal one, in mice treated with diethylnitrosamine promoted hepatocellular carcinoma development, increasing STAT3 activation and IL-6 production.…”
Section: Adipocyte-released Factors Strengthening Csc Chemotherapy Rementioning
confidence: 99%